2019
DOI: 10.1093/ije/dyz016
|View full text |Cite
|
Sign up to set email alerts
|

Association of menopausal characteristics and risk of coronary heart disease: a pan-European case–cohort analysis

Abstract: Background Earlier age at menopause has been associated with increased risk of coronary heart disease (CHD), but the shape of association and role of established cardiovascular risk factors remain unclear. Therefore, we examined the associations between menopausal characteristics and CHD risk; the shape of the association between age at menopause and CHD risk; and the extent to which these associations are explained by established cardiovascular risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 40 publications
11
53
1
Order By: Relevance
“…Trial data in younger women taking HRT (50-59 years) suggested no increased risk of cardiovascular disease, stroke or all-cause mortality 55 . In agreement with this we found no evidence to support causal associations for ANM with cardiovascular disease, lipid levels, Alzheimer’s disease, body mass or longevity ( Supplementary Table 23 ), all of which have been reported from non-genetic observational studies 6066 . Finally, we evaluated putative modifiable determinants of ANM suggested by previously reported observational studies.…”
Section: Resultssupporting
confidence: 79%
“…Trial data in younger women taking HRT (50-59 years) suggested no increased risk of cardiovascular disease, stroke or all-cause mortality 55 . In agreement with this we found no evidence to support causal associations for ANM with cardiovascular disease, lipid levels, Alzheimer’s disease, body mass or longevity ( Supplementary Table 23 ), all of which have been reported from non-genetic observational studies 6066 . Finally, we evaluated putative modifiable determinants of ANM suggested by previously reported observational studies.…”
Section: Resultssupporting
confidence: 79%
“…Overall, there was some evidence to suggest an association between early menopause and a higher risk of CVD events 5,21–24 and between late menopause and a lower risk of CVD events 5,17,20,21,23 after adjustment for age at menarche (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Heart disease is a leading cause of illness and death for women (Benjamin et al, 2019). Previous studies have examined the links between age at natural menopause or surgical menopause separately on the risk of incident CVD (Muka et al, 2016), but few have compared their effects (Dam et al, 2019). The extent that the risk of CVD varies by the type of menopause remains unclear.…”
Section: Introductionmentioning
confidence: 99%